'Men are not playing their roles', maternal and child nutrition in Nanoro, Burkina Faso. Issue 12 (1st August 2021) - Compaoré, Adélaïde; Ouedraogo, Kadija; Boua, Palwende R; Watson, Daniella; Kehoe, Sarah H; Newell, Marie-Louise; Tinto, Halidou; Barker, Mary; Sorgho, Hermann
Abstract: Objective: To collect context-specific insights into maternal and child health and nutrition issues, and to explore potential solutions in Nanoro, Burkina Faso. Design: Eleven focus groups with men and women from eleven communities, facilitated by local researchers. Setting: The study took place in the Nanoro Health district, in the West-Central part of Burkina Faso. Participants: Eighty-six men (18–55 years) and women by age group: 18–25; 26–34 and 35–55 years, participated in the group discussions. Results: Participants described barriers to optimal nutrition of mothers and children related to a range of community factors, with gender inequality as central. Major themes in the discussions are related to poverty and challenges generated by socially and culturally determined gender roles. Sub-themes are women lacking access to food whilst pregnant and having limited access to health care and opportunities to generate income. Although communities believe that food donations should be implemented to overcome this, they also pointed out the need for enhancing their own food production, requiring improved agricultural technologies. Given the important role that women could play in reducing malnutrition, these communities felt they needed to be empowered to do so and supported by men. They also felt that this had to be carried out in the context of an enhanced health care system. Conclusions: Findings reported here highlight the importance of nutrition-sensitive interventions and women's empowerment in improving maternal and child nutrition. There is a need to integrate a sustainable multi-sectorial approach which goes beyond food support.